2015
DOI: 10.1515/vtrr-2015-0007
|View full text |Cite
|
Sign up to set email alerts
|

Opinions Of Social Workers And Social Pedagogues About Their Professional Responsibility While Interacting With Clients

Abstract: Professional responsibility of social worker and social pedagogue is related to social, psychological, moral, educational, material and / or financial and other aspects. Then which aspects within the professional responsibility are worth to both specialists? The object of the research is the professional responsibility of social worker and social pedagogue. Research questions in this study are the following: What aspects are meaningful for social workers and social pedagogues within their professional responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…But our research results showed that this factor is not so important: students are not afraid of hard work and, on the contrary, working with children and daily challenges inspire them to choose this career. According to Jezerskytė & Žydžiūnaitė (2015), social pedagogues must realize themselves not only as professionals, but also as human beings who must find the ways to work with the diversity of clients. This means that the future social pedagogues must at first realize themselves as personalities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But our research results showed that this factor is not so important: students are not afraid of hard work and, on the contrary, working with children and daily challenges inspire them to choose this career. According to Jezerskytė & Žydžiūnaitė (2015), social pedagogues must realize themselves not only as professionals, but also as human beings who must find the ways to work with the diversity of clients. This means that the future social pedagogues must at first realize themselves as personalities.…”
Section: Discussionmentioning
confidence: 99%
“…Žydžiūnaitė & Crisafulli (2011Žydžiūnaitė & Crisafulli ( , 2012 were investigating the identity of the university students and the factors of the professional identity and the professional links with the curriculum. The recent research by Unauthenticated Download Date | 5/10/18 4:29 AM Jezerskytė & Žydžiūnaitė (2015) revealed the opinion of social educators about their professional responsibility while working with the clients. The researchers pointed out that social pedagogues, as being responsible professionals must realize themselves not only as professionals, but also as human beings who must find ways to connect with the diversity of clients.…”
Section: The Levels Of Social Pedagogy Students' Professional Identitymentioning
confidence: 99%
See 1 more Smart Citation